Identifikasi Sediaan Jamu Kuat yang Beredar di Kecamatan Banguntapan dan Pleret Kabupaten Bantul dengan Metode KLT - Dewi Umniyatul; Dwi Kurniawati Sambodo (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2019)
Background: Traditional herbs are ingredients or herbs in the form of plant material, animal ingredients, mineral ingredients, galenic preparations or mixtures of these ingredients, it has been used as medicine traditionally.Objective: This study is aimed to Identify of Sildenafil Citrate on “Jamu Kuat” (Herbal Medicine) products.Methods: This type of research was descriptive and the sample was determined by quota sampling. The method used Thin Layer Chromatography (TLC) which was a physicochemical method. There were seven samples were extracted by the soxhletation method until a thick extract was obtained to be spotted in the quite phase of TLC silica gel F254. The motion phase used to identify sildenafil citrate was chloroform: ethyl acetate (6: 4). Spots detection was done by observation under UV light 366 nm and the spots that appeared were calculated of Rf value and compared with the comparable Rf value of sildenafil citrate.Results: From this study, there were samples containing sildenafil citrate. Sample C with a sample Rf value of 0.75 and sample D with Rf value of sample 0.78 and a comparable Rf of sildenafil citrate 0.77.Conclusion: The seven samples of “Jamu Kuat” contained sildenafil citrate in Banguntapan and Pleret Districts, Bantul Regency. Keywords: Jamu Kuat (Herbal Medicine), Sildenafil citrate, TLC